Transformation of Entreprenurial University in The Face of Students' Expectations - Izabela CZAJA; Tomasz KAFEL (Communications of International Proceedings, 2021)
This article contributes to the debate on entreprenurial university and distance learning concepts. The research was conducted through loosely structured indepth interviews with students of Cracow University of Economics who had to change the way of learning and communicating with university environment in the forced situation of distance learning. The HEInnovate questionnaire was used to analyse the implementation of entrepreneurial university idea at Cracow University of Economics.The results of the survey suggests that distance learning is accepted as the teaching method and it is likely to be the relevant part of education in the future. The literature review and the results of interviews indicates the impact of digitalization on the education process will stay constance and it will require implementation a new aproach to handling the knowlege on both sides (techers and students). The aim of the article is to popularize the concept of an entrepreneurial university, and methods of measuring and assessing the entrepreneurship of higher education units.The application of the SCAMPER method to create a university model better suited to the needs of students was the purpose of the article too.
Keywords: Technological Dimension; Digital Transformation; Technological Potential; Entrepreneurial University; E-Learning; Univeristy in The Cloud